Strategi Teknologi Pembelajaran Pendidikan Agama Kristen: Antara Konvensional, Modern, dan Kreatif - Vriska Friyanti; Maria Titik Windarti (Journal on Education, 2024)
This paper discusses the integration of technology in Christian Religious Education (PAK) with a holistic approach that combines conventional, modern and creative elements. Based on the understanding that humans have the responsibility to create and use technology according to God's will, the TP-PAK learning strategy becomes the main focus. Involving conventional, modern and creative elements, this strategy aims to increase the effectiveness of PAK learning in facing technological developments in Indonesian society which is increasingly technologically cultured. This paper analyzes the PAK concept based on the Gangel, Benson, Homrighousen, and Graendorf approach, which provides a basis for developing learning technology strategies. PAK is considered important in shaping students' character, morals and spirituality, and the integration of technology is expected to enrich the learning experience. At the discussion and analysis stage, the paper outlines the steps for developing strategic ideas for PAK learning technology, including the application of technology in the context of PAK, the integration of conventional, modern and creative concepts, as well as implementation steps such as e-learning platforms and collaborative projects. Next, the paper analyzes the concept of PAK in depth and the importance of PAK in schools, and presents PAK learning strategies based on conventional approaches, discovery, mastery and investigation. The conclusion of this paper is that PAK learning strategies that integrate technology can create holistic and in-depth learning experiences. Implementation steps such as teacher training, cyber security awareness, parent participation, and integration of PAK with other subjects are the keys to success. Overall, this paper contributes to understanding and implementing PAK learning strategies that are relevant to technological developments in the digital era